Mediating role of coping styles on the relationship between personality types and mental disorders in cardiovascular patients: a cross-sectional study in Iran - Behzad Yaghoubi; Reza Nemati; Khosrow Agin; Ali Mohammad Beigi Dehaghi; Meysam Gazmeh; Farshad Rezaei; Elham Amirbandi; Akram Farhadi (BMC Psychiatry, 2023)
Abstract Background Many mental problems lead to the occurrence of physical diseases, causing worse consequences of diseases. Despite many studies in the field of personality types and types of mental disorders, this relationship and the mediating role of coping styles in cardiovascular patients are still not well known. Therefore, the present study was conducted to investigate the mediating role of coping styles in the relationship between personality types and mental disorders in cardiovascular patients. Method The present study is a cross-sectional study that was conducted on 114 cardiovascular patients at the heart center in Bushehr, Iran. The sampling method is simple random sampling. Demographic information form, MCMI-III questionnaire, NEO-FFI questionnaire, and Lazarus and Folkman coping styles questionnaire were used to collect data. Data were analyzed using SPSS 22 and Amos 24 software. Descriptive statistics methods (mean, variance and percentage), Pearson correlation, and structural equation model (SEM) were applied to analyze the data. Results The findings showed that the two variables of personality types and problem-oriented explain 15.2% of the variable of mental disorders, of which 10.7% is related to the variable of personality types and 4.5% is related to the intermediate variable of problem-oriented. Among the personality types, the neurotic personality type has the biggest role (0.632) and has a direct and significant effect on mental disorders. Also, the personality types of extroversion (-0.460), agreeableness (-0.312), and responsibility (-0.986) exert inverse and significant effects on mental disorders. Conclusion The results of the present study showed the frequency of personality disorders and other mental disorders among heart patients. Problem-oriented coping style plays a mediating role between personality types and mental disorders.